Developing multiple intelligence-based natural science learning module to improve elementary school students’ higher order thinking skills - Arrofa Acesta; Mohamad Syarif Sumantri; Fahrurrozi Fahrurrozi (Universitas Kuningan, 2020)
This study aims to develop a valid and effective natural science learning module based on multiple intelligences to improve high-level thinking skills of elementary school students. The type of research used was development research (R & D) which refers to the ADDIE, Dick and Carry models. A questionnaire sheet was used as instrument, consisting of 4 aspects, namely the feasibility of material, language, design, and media, as well as teacher and student response questionnaires. Based on the study, the results of the feasibility test by material experts obtained the feasibility of the product with a very good category, the feasibility test by a linguist with the product eligibility resulted in the very good category, the product feasibility test resulted by design experts were in the very good category, the feasibility test for the learning media expert was good, and the results of teacher and student assessments were in very good category. Furthermore, the results of the product truth test to students through the pretest and posttest showed that the products can improve student learning outcomes. From the calculation of the hypothesis test carried out, the significance results obtained were 0.00 <0.05, meaning that there were differences in student learning outcomes before and after using the science learning module. Based on the results of the hypothesis test, it can be denied that the science learning module based on multiple intelligence can improve students' higher order thinking skills in elementary schools.